2017
DOI: 10.1016/j.soc.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Future Clinical Trials

Abstract: SYNOPSIS The design of modern oncology clinical trials seeks to match patients’ cancer molecular biomarkers with medications that specifically target those biomarkers- a general paradigm shift in cancer care coined as “clinical cancer biology”1. This approach exploits the synthetic lethality between a specific genetic alteration in the cancer cell and a drug: rapid termination of exaggerated kinase activity (e.g. BCR-ABL, HER2 amplification), or irrevocable DNA damage (e.g. PARP inhibitors, platinum in BRCA-mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…However, we did not observe responses in two patients who received MTAs. This is consistent with the initial results of clinical trials looking at the use of MTAs in prospective fashion 33,34. For instance, in SAPHIR01 trial, for women with metastatic BC, 13% of patients were able to receive MTAs based on the genomic data and of those patients, only 9% had objective tumor response 35.…”
supporting
confidence: 82%
“…However, we did not observe responses in two patients who received MTAs. This is consistent with the initial results of clinical trials looking at the use of MTAs in prospective fashion 33,34. For instance, in SAPHIR01 trial, for women with metastatic BC, 13% of patients were able to receive MTAs based on the genomic data and of those patients, only 9% had objective tumor response 35.…”
supporting
confidence: 82%
“…To address these questions, a novel clinical design called a “basket trial” was developed. This is a new clinical trial paradigm that determines eligibility based on the presence of a specific genomic alteration, irrespective of histology (1, 47, 48). Unlike traditional clinical trials which focus on patients with a single cancer histology, the core organizing principle of basket trials focused on a specific genomic alteration found in the tumor, regardless of where the cancer originated (Figure 2).…”
Section: Basket Trialsmentioning
confidence: 99%
“…To this end, a novel clinical trial design referred to as a "basket trial", was developed. This study design focuses on specific gene alterations found in tumors, regardless of the location of cancer origins (6)(7)(8). Based on prior basket trials investigating the presence of specific gene alterations, a few of therapeutic strategies have been approved for pan-cancer patients independent of cancer types (i.e., larotrectinib for neurotrophic tyrosine kinase, receptor, type (NTRK) 1-3 fusion, pembrolizumab for mismatch repair high deficiency/ microsatellite instability, and pembrolizumab for high tumor mutation burden [TMB]; >10 mut/Mb]) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%